Pesticide Labeling: Storage and Disposal - Frederick M. Fishel (EDIS)
This document describes criteria that pesticide manufacturers consider when determining the proper storage and disposal language on their products' labels. Examples of typical storage and disposal statements are provided. This document is PI-106, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date March 2006.